Chronic systemic inflammation by peptidoglycan‐polysaccharide induces skeletal muscle atrophy in male and ovariectomized C57BL/6J mice - Ryoga Kinoshita; Jay Jung; Sakura Hattori; Tatsuhiro Yamaguchi; Takaya Kotani; Karina Kouzaki; Yuki Tamura; Koichi Nakazato (Physiological Reports)
Abstract Chronic systemic inflammation (CSI) induces skeletal muscle atrophy. The severity of tissue damage caused by CSI varies according to sex. However, there are still many unknowns regarding the sex differences in skeletal muscle atrophy in patients with CSI. This study aimed to determine the sex differences in CSI‐induced muscle atrophy using male and female C57BL/6J mice. 12‐week‐old mice were divided into peptidoglycan‐polysaccharide (PG‐PS) (each sex, n = 9) and control groups (each sex, n = 10). In the ovariectomy (OVX) study, 8‐week‐old female C57BL/6J mice were divided into sham, OVX + Saline, and OVX + PG‐PS groups (each group; n = 6). A single intraperitoneal injection of PG‐PS or saline was administered to the mice. After 3 weeks, blood and lower leg skeletal muscles were collected. Plasma inflammatory cytokine levels were significantly increased in both sexes following PG‐PS treatment. However, only male mice showed soleus muscle atrophy, decreased muscle protein synthesis (MPS), and increased apoptosis. In the OVX study, the OVX + PG‐PS group exhibited soleus muscle atrophy caused by PG‐PS‐induced CSI. In atrophic muscles, PG‐PS activated p65 and c‐Jun. These findings suggest that ovarian function regulates muscle protein metabolism and suppresses CSI‐induced skeletal muscle atrophy in female mice.